A Christian theology of Man as Co-Creator (Hekima Review, 2015)
Judeo-Christian theology is deeply rooted in the assumption that the world and all that it contains were created by one living God. The Book of Genesis tells us clearly that “In the beginning...the earth was a formless wasteland, and darkness covered the abyss, while the mighty wind swept over the waters” (Gen. 1: 2). God, then, brought all things into being through his powerful creative act. However, this divine creative act is presented to us in a hierarchised unity of reality with humankind occupying the highest and special place in it. It appears that humankind, in this hierarchy, depends on everything else; and everything else depends on humankind. us there is a symbiotic relationship. Furthermore, humankind has been given the divine mission by God himself to “dominate” and “subdue” nature. This article, therefore, grapples with the question of this divine mission or commission as assigned to humankind by God in relation to the ecological crisis that the world is facing at present.